Effect of MgO addition on the basicity of Ni/ZrO2 and on its catalytic activity in carbon dioxide reforming of methane (2009)
ABSTRACT: The effect of the MgO content on the basicity and on the catalytic performance of Ni/ZrO2–MgO catalysts for carbon dioxide reforming of methane was studied. MgO addition to the zirconia support by co-precip- itation (5% MgO) had several effects: stabilized the zirconia tetragonal phase by increasing its thermal stability, increased the basicity of the support, and decreased the reducibility of Ni2+. The CO2 desorption energy distribution functions calculated from the TPD-CO2 profiles were centred at activation energies around 100–134 kJ mol1. Besides the effect due to the modification of the zirconia properties by MgO addition, the catalytic activity was also related to the reduction degree of nickel on Ni/ZrO2–MgO cata- lysts, while the catalyst stability was related to the basic properties of the supports.